Response Characteristics of Sensor Array of Fresh Meat Detection Circuit using Conducting Polymer Sensor. Issue 1 (1st September 2022) - Hasrullah, Benrad Edwin Simanjuntak; Situmorang, Marhaposan; Humaidi, Syahrul; Sinambela, Marzuki
Abstract: Consumption of meat is needed by society. The meat needed is of course fresh and quality meat. However, the quality of meat sold in the community varies greatly. Fresh and quality meat is meat that is odorless, not slimy, does not change color in certain areas. Meat that is not fresh and not of good quality is smelly meat. The odor is described as a fishy smell, a foul smell, contains sulfur and smells like ammonia. Because it is dangerous to consume rotten meat, it is necessary to have an automatic meat detection device so that it can ensure the meat is fresh and of good quality. This tool replaces the human nose with an odor sensor as a bad smell detector.